2012
DOI: 10.1021/ic202623p
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic Mn and Co Complexes with a Large Polycyclic Aromatic Substituted Nitronylnitroxide

Abstract: 2-(1'-Pyrenyl)-4,4,5,5-tetramethyl-4,5-dihydro-1H-imidazole-3-oxide-1-oxyl (PyrNN) was reacted with M(hfac)(2) (M = Mn(II) and Co(II), hfac = hexafluoracetylacetonate) to give two isostructural ML(2) stoichiometry M(hfac)(2)(PyrNN)(2) complexes and a ML stoichiometry one-dimensional (1-D) polymer chain complex [Mn(hfac)(2)(PyrNN)]. The ML(2) complexes have similar crystal structures with monoclinic unit cells, in which one NO unit from each PyrNN ligand is bonded to the transition metal on cis vertices of a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 59 publications
5
24
0
Order By: Relevance
“…The cobalt–cobalt intrachain distance is 7.482(1) Å. The shortest interchain distance between cobalt(II) ions is a relatively large 11.151(1) Å, similar to that in the analogous isostructural manganese(II) chain (11.40 Å) 15. The crystallographic analysis of [Co(hfac) 2 PyrNN] n showed the substantial volume between individual chains to be occupied by entrained, disordered chloroform and n ‐heptane solvent molecules (for convenience, solvation molecules are not included in naming this complex).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The cobalt–cobalt intrachain distance is 7.482(1) Å. The shortest interchain distance between cobalt(II) ions is a relatively large 11.151(1) Å, similar to that in the analogous isostructural manganese(II) chain (11.40 Å) 15. The crystallographic analysis of [Co(hfac) 2 PyrNN] n showed the substantial volume between individual chains to be occupied by entrained, disordered chloroform and n ‐heptane solvent molecules (for convenience, solvation molecules are not included in naming this complex).…”
Section: Resultsmentioning
confidence: 83%
“…We recently reported that the PAH‐substituted nitronylnitroxide 2‐(1′‐pyrenyl)‐4,4,5,5‐tetramethyl‐4,5‐dihydro‐1 H ‐imidazole‐3‐oxide‐1‐oxyl (PyrNN) can be incorporated into a twofold helical [Mn(hfac) 2 PyrNN] n chain that has very strong antiferromagnetic exchange interaction between manganese(II) and the radical units, with no evidence of long‐range magnetic order down to 2 K 15. In this article, we report the isostructural cobalt(II) chain complex [Co(hfac) 2 PyrNN] n .…”
Section: Introductionmentioning
confidence: 99%
“…The calculated exchange interaction ( J calcd‐contact‐II / k B =−2.4 K) is small relative to the reported exchange interaction ( J / k B =−70 K) of Pyr−NN ⋅⋅⋅ NN−Pyr (Pyr: 1‐pyrenyl) with an intermolecular N−O ⋅⋅⋅ O−N contact of 3.374 Å . The difference between the two systems in the exchange interaction is due to the poor overlap of the nitroxide magnetic orbitals in [Cu(hfac) 2 (IN 2 Az)] ⋅ C 6 H 12 (see Figure S9)…”
Section: Resultsmentioning
confidence: 99%
“…[5][6] Lately the stable aminoxyl radicals attached to several polyaromatic hydrocarbons (PAH) have been synthesized and proved their application in rechargeable batteries, sensors, organic field effect transistors and quantum magnets. [7][8][9][10][11][12] The PAH bearing aminoxyl radical moieties are also found to exhibit photoexcited high spin states.…”
Section: Introductionmentioning
confidence: 99%